PENGARUH DIGITAL MARKETING, ELECTRONIC WORD OF MOUTH, DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE GLAD2GLOW PADA TOKO MY LOVA BENGKULU - Indriyani, Res; Ratnawili, Ratnawili (UM. Bengkulu, 2025)
This study aims to analyze the influence of digital marketing, electronic word of mouth (e-WOM), and lifestyle on the purchase decision of Glad2Glow skincare products at the My Lova Bengkulu Store. In addition, this study also seeks to identify the most dominant factors in influencing consumer purchase decisions. This research was conducted from November to December 2024 with a quantitative approach. The sample of this study is 170 consumers of Glad2Glow skincare products who shop at the My Lova Bengkulu Shop. The sampling technique used is probability sampling, so that every individual in the population has an equal opportunity to be selected as a respondent. Data analysis was carried out using the Multiple Linear Regression method processed through the SPSS 24 for Windows software. Based on the results of multiple linear regression, the regression equation form Y = 3.584 + 0.779 () + 0.171 (X2) + 0.285 (X3), where Y is the purchase decision, X₁ is digital marketing, X₂ is electronic word of mouth, and X₃ is lifestyle. In addition, the results of the analysis showed that the value of the determination coefficient (R Square, R²) was 0.858 or 85.8%, which means that the three independent variables together were able to explain 85.8% of the variability of the purchase decision, while the remaining 14.2% was influenced by other factors not included in this study. Based on the results of the research, it can be concluded that digital marketing, electronic word of mouth, and lifestyle have a positive and significant influence both partially and simultaneously on the purchase decision of Glad2Glow skincare products at the My Lova Bengkulu Store. Digital marketing is the most dominant factor in influencing consumer purchase decisions. These findings show that an effective digital marketing strategy, support from a good e-WOM, and the suitability of consumers' lifestyles with the products offered can improve skincare product purchase decisions. Keywords: Digital Marketing, Electronic Word Of Mouth, Lifestyle and Purchase Decisions.